Bioelectrical impedance vector analysis (BIVA) in university athletes - Priscila Custódio Martins; Luis Alberto Gobbo; Diego Augusto Santos Silva (Taylor & Francis Group, 2021)
Background Bioelectrical impedance vector analysis (BIVA) is able to identify differences in hydration status and body composition components, such as body cell mass (BCM) by means of plotting individuals in ellipses, when comparing groups with different characteristics. Objective Compare the confidence and tolerance ellipses of BIVA in individual and team sports athletes with a non-athlete reference population. Design and participants One hundred sixty-seven college athletes (team sports: 117 athletes, individual sports: 50 athletes) aged between 18 and 35 years. Bioelectrical impedance was used to measure resistance (R) and reactance (Xc) values that were used in the BIVA analysis to identify hydration status and BCM, respectively. Hotelling's t-test was used to identify differences between groups in the confidence ellipses and the comparison was made with a non-athlete Italian reference population. Results There were no differences between male team sports and individual athletes (p = 0.151) and for female athletes (p = 0.624). Most athletes were located in the 50% tolerance ellipses, indicating adequate hydration. Compared to the Italian a non-athlete population, athletes of both sexes presented left impedance vector deviation in the minor axis (Xc) of the tolerance ellipses, indicating higher BCM. Conclusion There were no differences in BIVA between team and individual sports athletes, but most athletes presented an adequate hydration state and, compared to a non-athlete population, the athletes of the present study presented higher BCM.